Distribution Activities At The Sungai Lulut Traditional Market As A Source of Learning Social Studies - Saputera, Yuli; Rahmia, Sovia Husni; Handy, Muhammad Rezky Noor; Triyono, Sigit; Nur'aini, Fatwa (Program Studi Pendidikan IPS, 2024)
The Sungai Lulut traditional market is a market in the Banjar Regency area, specifically in the Sungai Lulut sub-district. In this market there are economic activities that can be used as a learning resource. The learning process cannot be separated from the learning resources used. One of several learning sources that can be used is the environment. With regard to the environment, there is economic activity from the distribution around students that can be used as a learning resource in social studies learning. Learning resources that utilize existing economic activities in the market are still not optimally used by teachers because there are obstacles such as limited time, remote locations and inadequate facilities, even though they are very effective if used as learning resources. This research aims to describe the economic activities of distribution activities in the Sungai Lulut traditional market as a social studies learning resource. The approach used in this research is qualitative with descriptive methods. Data collection techniques through observation, interviews and documentation. Data analysis through data reduction, data presentation, and data verification. The data validity test used is triangulation of sources, techniques and time. The research results show that distribution activities in the Sungai Lulut traditional market are through direct and indirect distribution. Direct distribution, for example, risol traders and food stalls in the Sungai Lulut traditional market. This distribution activity is suitable for social studies learning as a learning resource for economic activity material, namely production, distribution and consumption at the even seventh semester grade junior high school level.